The Influence of Supervision of Learning and Work Climate on Performance State High School Teacher in Dharmasraya - Wakini Wakini; Adripen Adripen; Devy Aisyah; Suswati Hendriani; Demina Demina; Yetri Yetri (Budapest International Research and Critics University, 2022)
The purpose of this study was to find out the influence of learning supervision and work climate on State High School teachers in Dharmasraya. Research methods are used quantitative research with ex-post facto designs. The population in this study were all state high school civil servant teachers in Dharmasraya numbered 188. While the sampling technique is Probability Sampling (Proportional Stratified Random Sampling) with yamane formula with an error rate of 5% so that it gets a sample of 128. Research in the field shows that; (1) There is a significant influence on learning supervision on the teacher kiner with a t-count value of 9,110 with a t-table value of 1,979 with a significance value of 0.000 < 0.005. (2) There is no significant influence between the work climate on teacher performance on the basis of a t-count value of -0.129 < t-table value 1.97912 with a significance value of 0.533 > 0.005, (3) there is a significant influence on learning supervision and work climate simultaneously on teacher performance by 41.3% with a constant value of 238,194 with a coefficient of X1 of 1,218 and the price of coefficient X2 -0.129 with linear regression equation Y = a + b_1 X_1 + b_2 X_2 where Y = 238,194 + 1.218 〖 X〗_1+ -0.129 X_2. While from the test F simultaneously got a value of acquisition of significance F is 0.000 < 10 alpha (α) 0.05 with a value of F_hitung 44.030 > 〖 F 〗_tabel 3.07. So it can be concluded that learning supervision and work climate become variables that can affect the performance of State High School teachers in Dharmasraya.